Mathematical support for railway emergency response - Shalabayeva М.Х.; Akhmetov Б.С. (Bulletin of L.N. Gumilyov Eurasian National University Technical Science and Technology Series, 2021)
The current regulations provide a procedure for notification of the occurrence of railway emergencies, but do not define a procedure for responding to such situations. This can be explained by the fact that such situations are very diverse in nature and scale, as well as in the way they are handled. However, the more urgent is the need for a certain classification, typification of ways to respond to them. In connection with the above, the article shows that in the event of occurrence of WD AS, the head of the operational headquarters in complex conditions of lack of complete and sufficient information on cause-and-effect relations between components of such a situation should take a certain number of individual, collegial, information, organizational, operational decisions aimed at coordination, coordination and management of subordinate control points and response units, which may exceed his ability to make such decisions and / or influence their validity.